Lysine Residues Are Not Required for Proteasome-Mediated Proteolysis of the Auxin/Indole Acidic Acid Protein IAA1. Issue 2 (17th April 2015) - Gilkerson, Jonathan; Kelley, Dior R.; Tam, Raymond; Estelle, Mark; Callis, Judy
Abstract : Ubiquitin attachment to nonlysine sites on a transcriptional repressor implies a diversity in ubiquitination linkages. Abstract: Although many ubiquitin-proteasome substrates have been characterized in plants, very little is known about the corresponding ubiquitin attachment(s) underlying regulated proteolysis. Current dogma asserts that ubiquitin is typically covalently attached to a substrate through an isopeptide bond between the ubiquitin carboxy terminus and a substrate lysyl amino group. However, nonlysine (non-Lys) ubiquitin attachment has been observed in other eukaryotes, including the N terminus, cysteine, and serine/threonine modification. Here, we investigate site(s) of ubiquitin attachment on indole-3-acetic acid1 (IAA1), a short-lived Arabidopsis ( Arabidopsis thaliana ) Auxin/indole-3-acetic acid (Aux/IAA) family member. Most Aux/IAA proteins function as negative regulators of auxin responses and are targeted for degradation after ubiquitination by the ubiquitin ligase SCF TIR1/AFB (for S-Phase Kinase-Associated Protein1, Cullin, F-box [SCF] with Transport Inhibitor Response1 [TIR1]/Auxin Signaling F-box [AFB]) by an interaction directly facilitated by auxin. Surprisingly, using a Histidine-Hemaglutinin (HIS6x -HA3x ) epitope-tagged version expressed in vivo, Lys-less IAA1 was ubiquitinated and rapidly degraded in vivo. Lys-substituted versions of IAA1 localized to the nucleus as Yellow Fluorescent Protein fusions and interacted with both TIR1 and IAA7 in yeast ( Saccharomyces cerevisiae ) two-hybrid experiments, indicating that these proteins were functional. Ubiquitination on both HIS6x -HA3x -IAA1 and Lys-less HIS6x -HA3x -IAA1 proteins was sensitive to sodium hydroxide treatment, indicative of ubiquitin oxyester formation on serine or threonine residues. Additionally, base-resistant forms of ubiquitinated IAA1 were observed for HIS6x -HA3x -IAA1, suggesting additional lysyl-linked ubiquitin on this protein. Characterization of other Aux/IAA proteins showed that they have diverse degradation rates, adding additional complexity to auxin signaling. Altogether, these data indicate that Aux/IAA family members have protein-specific degradation rates and that ubiquitination of Aux/IAAs can occur on multiple types of amino residues to promote rapid auxin-mediated degradation.